Spatial Variability of Water and Sediment Quality in Pond Outlet: Implications for Coastal Ecosystems in Mangrove Areas, Pasuruan, East Java - Rizky, Putri Nurhanida; Halim, Atika Marisa; Nisa, Andina Chairun; Prama, Ega Aditya; Ulfauza; Oktahimawan, Muhammad Khusni (Bogor Agricultural University, Indonesia, 2025)
Aquaculture expansion in Pasuruan's coastal areas raises concerns about water and sediment pollution, but the spatial variability and magnitude of these impacts remain insufficiently quantified. This study aimed to assess the water and sediment quality at pond outlets across different aquaculture systems. Samples were collected from seven intensive (high-input shrimp farming), traditional (low-input, extensive ponds), and silvofishery (integrated aquaculture with mangroves) aquaculture farms from July to September 2024, coinciding with peak farming activity. Water and sediment samples were collected from seven farms and analyzed for chemical parameters, organic matter content, and redox potential. Results of the current research record extensive spatial and temporal heterogeneity that is driven by aquaculture management and external events like the WSSV epizootic in August 2024. Ammonia concentrations increased dramatically at stations within intensive vannamei shrimp farms (5.5 mg/L), while downstream stations exhibited natural dilution and mitigation by mangroves. Sediment quality analysis demonstrated a reducing condition with redox potential values from as low as -100 mV and SOM concentrations as high as 23%. Correlation analysis highlighted intensive farming systems as the main drivers of water and sediment degradation, with mangrove belts demonstrating resistance through nutrient adsorption and filtration with COD, TSS, and organic matter as primary pollution contributors. These findings emphasize the urgent need for adopting sustainable practices, such as polyculture systems, reduced feed input strategies, the implementation of constructed wetlands, and enhanced mangrove rehabilitation around aquaculture zones, to minimize environmental impacts and preserve coastal ecosystem health.